Direct measurements of lift and drag on shallowly submerged cobbles in steep streams: Implications for flow resistance and sediment transport. Issue 9 (1st September 2017) - Lamb, Michael P.; Brun, Fanny; Fuller, Brian M.
Abstract: Steep mountain streams have higher resistance to flow and lower sediment transport rates than expected by comparison with low gradient rivers, and often these differences are attributed to reduced near‐bed flow velocities and stresses associated with form drag on channel forms and immobile boulders. However, few studies have directly measured drag and lift forces acting on bed sediment for shallow flows over coarse sediment, which ultimately control sediment transport rates and grain‐scale flow resistance. Here we report on particle lift and drag force measurements in flume experiments using a planar, fixed cobble bed over a wide range of channel slopes (0.004 <  S  < 0.3) and water discharges. Drag coefficients are similar to previous findings for submerged particles ( CD ∼ 0.7) but increase significantly for partially submerged particles. In contrast, lift coefficients decrease from near unity to zero as the flow shallows and are strongly negative for partially submerged particles, indicating a downward force that pulls particles toward the bed. Fluctuating forces in lift and drag decrease with increasing relative roughness, and they scale with the depth‐averaged velocity squared rather than the bed shear stress. We find that, even in the absence of complex bed topography, shallow flows over coarse sediment are characterized by high flow resistance because of grain drag within a roughness layer that occupies a significant fraction of the total flow depth, and by heightened critical Shields numbers and reduced sediment fluxes because of reduced lift forces and reduced turbulent fluctuations. Plain Language Abstract: Steep mountain streams have slower flow and they transport less sediment as compared to lower gradient rivers. Often these observations are attributed to complex river‐bed geometries, but little work has explored steep rivers with simple, flat riverbeds. To address this gap in observations, we performed a series of experiments in a controlled indoor river facility and measured directly the forces that flowing water imparts on streambed cobbles and boulders. Under the shallow, rough water flows common to mountain streams, we found that downstream oriented drag forces significantly increase in shallow flow. On the contrary, vertically oriented forces pull the cobbles towards the river bed, rather than the more common scenario where they lift sediment off the bed. We also observed a lower intensity of turbulence in steep rivers, despite the vigorous appearance of the water. Combined, these observations help to explain reduced water flow and sediment transport rates in mountain rivers. Key Points: Direct measurements of lift and drag forces were made on cobbles in steep flume experiments with shallow, rough flow over a planar bed As flows shallow, drag coefficients increase, turbulent fluctuations decrease, and lift forces are negative, pulling particles to the bed Results help explain high flow resistance, high critical Shields numbers, and low sediment transport rates in mountain streams